A Study on the Dynamic Analysis of Snowboarding Turn - YAMADA, Tomoaki; DOKI, Hitoshi; HOKARI, Masaki; NAGAI, Chikara (Transactions of the Japan Society of Mechanical Engineers Series C, 2006)
The main goal of this study is to establish the measurement system which enables kinematics analysis of snowboarding turns on an outside snow field and to analyze and evaluate the kinetics. The measurement system consists of the 6-axis force sensor which measures reaction force from the snow surface, motion tracking sensor to obtain the movement data of upper body and lower limb and image analysis system which can provide kinematics data of snowboarder on wide range. By applying this measurement system, the quantification of physical exertion on each phase of a snowboard turn and the estimation of joint moments were performed. The fact that this measurement system can analyze major feature of snowboarding turn makes it an effective method for suggesting more ideal turn form, prevention of the disorder and injury from snowboarding and development of snowboarding kits such as board and binding and so on.